Pengaruh pembelajaran berbasis masalah terhadap efikasi menulis ilmiah mahasiswa (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2019)
This study aims to evaluate the impact of a scientific writings course conducted with a problem-based learning model to improve the efficacy of students in scientific writing and understanding of scientific writing procedures. Subject of research consist 31 students in Guidance and Counseling Department. The results showed an increase in students understanding about procedures on compose a scientific papers and also experienced a significant increase overall and in every aspect of the efficacy tested.